PENGARUH MEDIA SOSIAL TERHADAP USIA MENARCHE PADA SISWI SEKOLAH MENEGAH PERTAMA DI KOTA KOTAMOBAGU - Agustin Agustin; Sitti Nurul Hikma Saleh (GEMA KESEHATAN, 2021)
Social media is a medium that is very easy to use to spread various information. Mass media and social media have been used to distribute information to each other. Heavy exposure to social media can accelerate sexual hormone maturity, causing early menarche in adolescent women. This research was conducted on July 13, 2021, to know the effect of social media on the age of menarche in junior high school students. This research method uses descriptive-analytic research. Using the purposive sampling technique, samples were taken off as many as 61 respondents. The independent variable is social media, and the dependent variable is the age of menarche for junior high school students. The analysis was used in univariate and bivariate with Chi-square test. This study shows a relationship between the influence of social media on the age of menarche in junior high school students in Kotamobagu City (p-value = 0.000). This study concludes that social media affects the age of menarche in junior high school students in Kotamobagu City. It is suggested that the school provide health education to increase knowledge about reproductive health in adolescent girls, especially menarche.